Numerical modelling of interaction of cemented natural fractures and hydraulic fractures - Haiyang Wang; Peiyao Xiao; Desheng Zhou; Qingqing Wang (Scientific Reports)
Abstract Cemented natural fractures (CNFs) are commonly found in unconventional shale and tight sandstone reservoirs. During the process of hydraulic fracturing, CNFs can affect the propagation of hydraulic fractures and thus impact oil and gas production. However, the interaction behavior between CNFs and hydraulic fractures is still unclear. In this study, a fully fluid-solid coupling numerical model simulating hydraulic fracture propagation was developed to simulate the interaction propagation of hydraulic fractures and CNFs based on the particle flow method. The numerical model results are in good agreement with published experimental results, indicating the reliability of the model. The model was used to analyze the effects of natural fracture cementation strength, inclination angle, and fracturing fluid viscosity on the interaction propagation morphology of fractures. The influence of induced stress fields on the interaction propagation of fractures was also studied. The simulation results indicate that the CNF with different inclination angles may have different critical cementation strength ratios. When the cementation strength ratio is relatively small, the hydraulic fracture is arrested by the CNF, the CNF is opened, generating significant shear fractures. A new fracture propagation pattern was discovered in this study, where the hydraulic fracture is arrested by the weakly CNF and generates bifurcation fractures that communicate with the tips of the natural fracture. Additionally, low viscosity fracturing fluid facilitates the generation of complex fracture networks during the interaction propagation of the hydraulic fracture and the weakly CNF.